2020
DOI: 10.1021/acs.orglett.0c03892
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Nickel-Catalyzed P(O)–C(sp2) Coupling Using Thioxanthen-9-one as a Photoredox Catalysis

Abstract: An efficient method has been developed for photocatalytic P­(O)–C­(sp2) coupling of (hetero)­aryl halides with H-phosphine oxides or H-phosphites under the irradiation of visible light or sunlight. The thioxanthen-9-one/nickel dual catalysis mediates this phosphonylation to give arylphosphine oxides and arylphosphonates in moderate to excellent yields. This transformation is widely tolerant to a range of functional groups and proceeds efficiently on a gram scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…In addition, the easily generated alkenyl and aryl C-O electrophiles are attractive in photoredox and transition metal dual catalysis. In 2017, Liao et al [95] reported a phosphorylation of alkenyl and aryl C-O bonds at room temperature via photoredox/nickel dual catalysis [Figure 62]. Diverse structurally important alkenyl phosphonates and aryl phosphine oxides are generated in moderate to excellent yields.…”
Section: Transition Metal/photoredox Dual Catalyzed Phosphorylation Reactions Of (Pseudo)halidesmentioning
confidence: 99%
“…In addition, the easily generated alkenyl and aryl C-O electrophiles are attractive in photoredox and transition metal dual catalysis. In 2017, Liao et al [95] reported a phosphorylation of alkenyl and aryl C-O bonds at room temperature via photoredox/nickel dual catalysis [Figure 62]. Diverse structurally important alkenyl phosphonates and aryl phosphine oxides are generated in moderate to excellent yields.…”
Section: Transition Metal/photoredox Dual Catalyzed Phosphorylation Reactions Of (Pseudo)halidesmentioning
confidence: 99%
“…Spectroscopic data were consistent with previously published data. 37 1 H NMR (400 MHz, CDCl 3 ) δ 7.49 (td, J = 7.4, 2.4 Hz, 4H), 7.58 (t, J = 7.4 Hz, 2H), 7.66 (dd, J = 12.4, 7.4 Hz, 4H), 7.72 (dd, J = 8.4, 2.4 Hz, 2H), 7.82 (dd, J = 11.2, 8.4 Hz, 2H); 13 C{ 1 H} NMR (101 MHz, CDCl 3 ) δ 123.7 (q, 1 J CF = 273.6 Hz, CF 3 ), 125.5 (dq, 3 J CP = 12.0 Hz, 3 J CF = 3.8 Hz, 2 × CH), 128.9 (d, 3 J CP = 12.3 Hz, 4 × CH), 131.8 (d, 1 J CP = 105.4 Hz, 2 × C), 132.2 (d, 2 J CP = 10.1 Hz, 4 × CH), 132.5 (d, 4 J CP = 2.8 Hz, 2 × CH), 132.7 (d, 2 J CP = 10.1 Hz, 2 × CH), 133.8 (qd, 2 J CF = 32.9 Hz, 4 J CP = 2.9 Hz, C), 137.3 (d, 1 J CP = 101.2 Hz, C); MS (ESI) m / z 369 (M + Na + , 100).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…36 Later, the Yu group reported phosphorylation of alkenyl and aryl C–O bonds via similar dual catalytic systems. 37 More recently, the heterogeneous photocatalyst CdS 38 and organic thioxanthen-9-one 39 were also found to be competent to enable this nickel metallaphotocatalytic conversion. 40–43 As for the Ni/photoredox catalyzed C–S construction, 44,45 in 2016, Johannes and co-workers developed a NiCl 2 /Ir[dF(CF 3 )ppy] 2 (dtbbpy)PF 6 mediated cross-coupling reaction of thiols with aryl iodides.…”
Section: Introductionmentioning
confidence: 99%